Ostomy self-management experiences of people with an ostomy: a scoping review - Sham, Fatimah; Abdul Wahab, Patimah; Che Hasnan, Luqman Wafi; Setiawan, Estriana Murni (e-International Publishing House, 2025)
This scoping review examines ostomy self-care as a multidimensional concept encompassing physical, psychological, social, and spiritual aspects, but lacking a consistent framework. Key facilitators include family support, culturally sensitive education, telehealth, and spiritual care, while barriers involve body image concerns, stigma, physical complications, and limited specialized care access. The review highlights inconsistent terminology and classification, emphasizing the need for standardized definitions and assessment tools. Holistic, individualized care strategies that address all dimensions of self-care are essential. Future research should focus on standardization and long-term support to enhance independence and quality of life for people living with an ostomy